Distribuer la chaleur fatale des entreprises : la construction dynamique d’un réseau d’énergie décarbonée, entre flux et infrastructure - Zélia Hampikian (Développement Durable et Territoires)
The recovery of waste heat is increasingly promoted as an instrument for climate change mitigation and energy transition. However, when such a flow is distributed by a heat network, the stakeholders in charge of the network operation do not have control over the flow production. This article aims at understanding the consequences of this lack of control on the construction and running of a network through the analysis of two French case studies in Dunkirk and the Val d’Europe. It shows that the temporal evolution of the heat flow and the projections that the actors make of it lead the decisions taken regarding the network. Hence, the produced flow is put at the center of the network evolution rational and the infrastructure is built accordingly to distribute it. In that sense, the process is inverted from the classic rational of the construction of urban networks.